Factors that influence the implementation of empowerment in hospitality industry - Che, Chow Lin @ Gowri (Universiti Malaysia Sarawak (UNIMAS), 2003)
The purpose of this study was to determine the perception of middle managers in hotels towards the implementation of empowerment and the factors that influence it. Specifically the objective of the study is to determine if there is any difference among middle managers with vaned demographic characteristics such as gender, academic qualification and years of service in term of their perception towards the implementation of empowerment in hotel. The other objective was to determine whether there is any significant relationship between the implementation of empowerment and factors such as communication, coaching and participation. Survey research methodology was used for the purpose of data collection. The respondent was 46 middle managers from 4and 5 star hotels in Penang Island. Stratified sampling was used to determine the minimum sample size that required for the study. Questionnaire consist of two sections were used as the instrument. The first part consists of questions more to demographic characteristics. Items in the second section question on the perception of middle managers towards the implementation of empowerment and factors that influence it. Statistical tests such as Independent Sample T-test, one-way ANOVA and Pearson Bivariate Correlation method were used. The study found that the majority (80.40%) of middle managers in six hotels have a positive perception towards the implementation of empowerment. the study also show that there is no significant difference among middle mangers in term of their perception toward the implementation of empowerment in hotel based on their gender (t=0.245,p=0.808), academic qualification (F=0.344,p=0.793) and years of service (F=O.796,p=0.559). The Pearson Correlation Coefficient Analysis also indicates that there is significant relationship between the implementation of empowerment and factors such as communication (r=O.647, p<O.Ol), coaching (r=0.634,p <0.01) and participation (r=0.478,p<0.01). Findings of the study show that that the middle managers ability to communicate, coach and participate as involvement will lead to the successful implementation of empowerment in hotel. The multidimensional task of the middle managers plays an important role in the success on implementing empowerment.